Directive Speech Acts and Speaking Strategies of Teachers in Biography Text Learning - Fani Indah Kurniawati; Ermawati Arief; Ena Noveri; Herlin Triana (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to describe the forms of directive speech acts and speaking strategies used by Indonesian language teachers during biography text learning in Grade X of SMA Negeri 1 Ampek Angkek. This research employed a qualitative approach with descriptive methods. Data were collected from January 27 to February 10, 2026, across four meeting sessions. The data sources consisted of oral utterances produced by the Indonesian language teacher, Ibu Revvi Mithania, S.Pd., M.Pd., Gr., during classroom interactions. Data collection techniques included non-participant observation (SLBC), note-taking, and audio-video recording. Data validation used triangulation techniques involving the researcher, the academic supervisor, and a language expert. The analysis involved transcription, identification, classification, and interpretation of directive utterances. The findings revealed 203 directive speech act utterances comprising six forms: (1) questioning with 106 utterances (52.2%), (2) ordering with 64 utterances (31.5%), (3) requesting with 2 utterances (1.0%), (4) demanding with 14 utterances (6.9%), (5) advising with 12 utterances (5.9%), and (6) challenging with 5 utterances (2.5%). Regarding speaking strategies, four strategies were identified: (1) bald on-record (BTTB) with 139 utterances (68.5%), (2) positive politeness (BTBKP) with 54 utterances (26.6%), (3) negative politeness (BTBKN) with 5 utterances (2.5%), and (4) off-record (BSS) with 5 utterances (2.5%). The off-heart strategy (BDH) was not found. The dominant use of the questioning form and the bald on-record strategy indicates that the teacher prioritized direct and efficient communication during biography text learning.